Implementasi Undang-Undang Perkebunan dalam Penanganan Pencurian Hasil Kebun Kelapa Sawit di Wilayah Hukum Polres Langkat - Tanjung, Master Sahat Maruli Tuah Purba; Zulyadi, Rizkan; Siregar, Taufik (Mahesa Research Center, 2023)
The purpose of this study is to analyze the legal rules regarding theft in Indonesia, the implementation of the Plantation Law in handling the theft of oil palm plantations and the obstacles in the Langkat Police Legal Area. The research method used by the author is normative juridical by finding and collecting data through library research from reading sources in the form of legal books, legal expert opinions, laws and regulations, websites, and interview results. The results of the study show that the legal rules regarding palm oil theft in Indonesia are regulated in Article 107 Letter d of Law No.39 of 2014 concerning Plantations. In its application, any person who illegally harvests and/or collects plantation products shall be sentenced to a maximum imprisonment of 4 (four) years and a maximum fine of Rp. 4,000,000,000, - (four billion rupiah) and this is if the victim is a company that has a land area of more than 25 ha and already has a plantation permit from the government, but for cases where the victim is an individual, the article is not subject to the regulation of the Supreme Court, and countermeasures with preventive efforts where the handling focuses on prevention or control before the occurrence of the crime of theft. Repressive efforts are more in the nature of prosecution or eradication after the criminal act of theft of Oil Palm Fresh Fruit Bunches.